Subsoiling before winter wheat cultivation increases photosynthetic characteristics and leaf water-use efficiency of summer maize in a double-cropping system. Issue 6 (12th May 2023) - Jiao, Fengli; Hong, Shengzhe; Zhang, Qingfen; Li, Ming; Shi, Ruilin; Ma, Yuzhao; Li, Quanqi
ABSTRACT: Long-term rotary tillage negatively affects the soil plow layer, and subsoiling is an effective engineering measure to improve the structure of the soil plow layer. A double cropping system with winter wheat and summer maize is commonly practiced in the North China Plain (NCP). Three different tillage treatments, viz., rotary tillage at 15 cm (RT15) as control, and subsoiling at depths 35 cm (SS35) and 40 cm (SS40) were carried out during the 2017–2019 summer maize growing seasons, before winter wheat planting. We determined these tillage treatments on chlorophyll content index (CCI), leaf area index (LAI), net photosynthetic rate (Pn), transpiration rate (Tr), and grain yield (GY) across three seasons. Subsoiling treatments significantly increased the CCI, LAI, Pn, Tr and water-use efficiency of leaves (WUEL ), resulting in higher GY. Compared to the plants grown in the SS40 group, the CCI and LAI were improved during the late growth stages, kernel numbers per row and 1000-grain weight of plants in SS35 were significantly higher, thereby improving GY (by 2.87%) and WUEL (by 6.61%). These results suggest that subsoiling to a depth of 35 cm improved photosynthetic characteristics and water use efficiency of summer maize in the NCP.